MiR‐34b Modulates Skeletal Muscle Cell Proliferation and Differentiation. Issue 12 (14th July 2017) - Tang, Zhixiong; Qiu, Huiling; Luo, Lan; Liu, Nian; Zhong, Jiasheng; Kang, Kang; Gou, Deming
ABSTRACT: Myogenesis involves myoblast proliferation and differentiation to myocytes, followed by fusion and hypertrophy to form myotubes during muscle development. Increasing evidence showed that microRNAs (miRNAs) play important roles in the regulation of myogenesis. We have previously revealed that miR‐34b is steadily increased during this process. This miRNA regulates differentiation in various cell types, though its function in myogenesis remains to be elucidated. In this study, we show that miR‐34b represses muscle cell proliferation and promotes myotube formation. Our quantitative iTRAQ‐based proteomic analysis reveals 97 proteins are regulated by miR‐34b in mouse myoblast C2C12. We identified that miR‐34b targets 14‐3‐3 protein gamma, adenosylhomocysteinase and nucleolin by binding to their 3′UTR. Further analysis of these proteins expression patterns show that nucleolin is a cognate target of miR‐34b during myogenic differentiation. Here, we proved that a moderate reduction of nucleolin in cells enhanced the myotube formation. However, nucleolin is required for myogenesis, as cells with low levels of nucleolin reduced cell proliferation rate and are unable to differentiate. Our data demonstrated that nucleolin regulates myogenesis in a protein‐abundance‐dependent manner. J. Cell. Biochem. 118: 4285–4295, 2017. © 2017 Wiley Periodicals, Inc. Abstract : miR‐34b is steadily increased during myogenic differentiation, represses muscle cell proliferation and promotes myotube formation. Nucleolin is a cognate target of miR‐34b during myogenic differentiation and regulates myogenesis in a protein‐abundance‐dependent manner.